2015
DOI: 10.3389/fnbeh.2015.00215
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modafinil on the rat dopamine transporter and dopamine receptors D1–D3 paralleling cognitive enhancement in the radial arm maze

Abstract: A series of drugs have been reported to increase memory performance modulating the dopaminergic system and herein modafinil was tested for its working memory (WM) enhancing properties. Reuptake inhibition of dopamine, serotonin (SERT) and norepinephrine (NET) by modafinil was tested. Sixty male Sprague–Dawley rats were divided into six groups (modafinil-treated 1–5–10 mg/kg body weight, trained and untrained and vehicle treated trained and untrained rats; daily injected intraperitoneally for a period of 10 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 55 publications
1
16
0
1
Order By: Relevance
“…Modafinil was a moderate and relatively selective DAT inhibitor, with an IC 50 value of 11 µM. This finding is consistent with previous in vitro studies that reported IC 50 values of 4-13 µM (Karabacak et al, 2015;Loland et al, 2012;Madras et al, 2006;Zolkowska et al, 2009). The interaction between modafinil and DAT is also thought to modulate the pharmacological effects of the drug (Wisor, 2013).…”
Section: Monoamine Uptake Transporter Inhibition and Monoamine Effluxsupporting
confidence: 89%
“…Modafinil was a moderate and relatively selective DAT inhibitor, with an IC 50 value of 11 µM. This finding is consistent with previous in vitro studies that reported IC 50 values of 4-13 µM (Karabacak et al, 2015;Loland et al, 2012;Madras et al, 2006;Zolkowska et al, 2009). The interaction between modafinil and DAT is also thought to modulate the pharmacological effects of the drug (Wisor, 2013).…”
Section: Monoamine Uptake Transporter Inhibition and Monoamine Effluxsupporting
confidence: 89%
“…Multiple neurotransmitter systems have been implicated in modafinil activity [10,58], as several studies have reported significant occupancy of NET, beside activity at DAT [59]. Hence, in cells expressing human DAT, R-modafinil inhibits DAT (IC 50 6.4-13 µM) and NET activity (IC 50 35.6-182 µM), albeit with lower potency in the case of the latter [34,60,61]. On the other hand, (S)-CE-123 shows negligible activity at NET or SERT, and blocks DAT (IC 50 = 4.6 µM) without acting as a substrate [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since pain relief has been recognized as a human right17 and considered as the “fifth” vital sign to be routinely assessed, nurses should give great attention to control postoperative pain 18. Nurses working in the surgical unit should have an adequate level of knowledge regarding different treatment modalities and their technique of administration 19. They should also consider patients’ self-report of pain which is the best to evaluate pain perceptions and cognitive response 20.…”
Section: Introductionmentioning
confidence: 99%